Perinatal and Childhood Outcomes Associated with Infertility - Zore, Temeka; Wang, Erica T. (Seminars in Reproductive Medicine, 2017)
Infertility affects 11% of reproductive-age women in the United States and the number of live births from infertility treatment, both in vitro fertilization (IVF) and non-IVF fertility treatment (NIFT), continues to rise. Given this trend, the perinatal and childhood outcomes of children conceived with assisted reproduction are of critical importance. We provide a comprehensive overview of the current literature, consisting primarily of observational cohort studies focused on IVF children. The outcomes of interest include (1) perinatal outcomes of low birth weight and prematurity; (2) congenital birth defects; (3) childhood development to encompass autism spectrum disorders, development, and school functioning; (4) growth and puberty: and (5) childhood cancer. Overall, these data appear to be reassuring; however, further studies are needed to clarify the role of underlying parental infertility and to focus on NIFT conceptions. There remains a paucity of long-term data for these children as they progress to adulthood and long-term prospective registries will be the key to answering these questions.
Keywords: perinatal outcomes; infertility; IVF; NIFT